Features of Formation of Infrastructure of Digital Nomadism on the Route of the Great Tea Road through the Western Siberia and the Central Urals - BALUK, Natalia A.; BALUK, Aleksey D.; KUPRIN, Anatoly S.; KUPRINA, Lidia Y.; SITEVA, Svetlana S.; BELONOZHKO, Marina L. (Journal of Environmental Management and Tourism; Vol 8 No 4 (2017): JEMT Volume VIII Issue 4(20) Summer 2017, 2017)
This article discusses options for providing digital nomadism with tourist services in the conditions of the Siberian city of Tyumen. In order to improve the mobility of this category of tourists, the authors propose a model of information support itinerary "The Great Tea Road: Siberian Highway" Navigation System Information Depository is focused on the localization of points of life support systems and free Wi-Fi with the optimum combination of infrastructure and cultural heritage. To fill an information depository of tourist destination of Tyumen conducted the identification and annotation of the most significant natural and cultural heritage, attractors, viewing platforms has been conducted. When selecting these objects the authors based on the following fundamental principles: accessibility of facilities to the exit to the Internet system sources; consumer preferences; security. In order to ensure the quality of tourist services the analysis of the infrastructure of guest service in Tyumen is undertaken in the article. The study developed proposals for implementation of the model of information depositary. The information field of the depositary includes the system of orientation markers in space, providing the connection of the location of the object with geoinformation field. In general, the proposed model, as the authors believe, will contribute to a comfortable and safe adherence to digital nomads on the tourist route.